PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT UMUM DAERAH KABUPATEN POHUWATO - Sulaiman Sulaiman (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
The effect of service quality on patient satisfaction in the District General Hospital Pohuwato. The results of the analysis of data obtained by the equation Y = -0.494 + 1.242 X. From this simple regression equation, it was explained that the value of a fixed value of -0.494 represents the level of satisfaction obtained by the patients at the General Hospital District Pohuwato if the quality of service to patients is negligible. While the coefficient of the variable quality of service 1.242 magnitude can be explained, that if the quality of service to the District General Hospital Pohuwato increased by one unit, the patient satisfaction will increase by 1.242 units or in other words the quality of care for patient satisfaction at the District General Hospital Pohuwato positive or direct at 1.242. The coefficient of determination or coefficient r2 penententu the disimbol to explain the contribution of service quality on patient satisfaction in the District General Hospital Pohuwato. From the results of processed data obtained value r2 = 0.670 or 67%, thus the contribution to the quality of patient satisfaction waitress at District General Hospital Pohuwato is 67% and in the large category. Analysis of the relationship between the variables of service quality and patient satisfaction at the District General Hospital Pohuwato processed as indicated in the attached data value r = 0.818 or 81.8% indicating that the relationship between the variables of service quality with variable patient satisfaction at the Regional General Hospital District Pohuwato is very closely ie 81.8% and significant.